1994
DOI: 10.3382/ps.0730089
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Transovarian Transmission of Salmonella enteritidis in Laying Hens

Abstract: To understand the mechanism of transovarian transmission of Salmonella enteritidis in laying hens, experiments were conducted to examine the isolation of S. enteritidis from the preovulatory follicles of experimentally infected hens. Salmonella enteritidis was isolated from the preovulatory follicles in 16 birds (from follicle membrane alone in 10 birds, from the follicle yolk alone in 4 birds, and from both membrane and yolk in 2 birds). In addition, 83 S. enteritidis isolates of the major phage types prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(55 citation statements)
references
References 28 publications
(21 reference statements)
1
50
0
4
Order By: Relevance
“…This is surprising since, after infection, localization in the reticulo-endothelial system takes place rapidly. It is possible that infection may actually occur in the ovules, perhaps as part of the preovulatory follicle membrane, as has been suggested for S. Enteritidis (Thiagarajan et al, 1994), and that infection does not appear in eggs until the ovules mature sufficiently to enter the oviduct and become part of an egg. This does not completely preclude involvement of the oviduct in infection as may also occur with S. Enteritidis.…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising since, after infection, localization in the reticulo-endothelial system takes place rapidly. It is possible that infection may actually occur in the ovules, perhaps as part of the preovulatory follicle membrane, as has been suggested for S. Enteritidis (Thiagarajan et al, 1994), and that infection does not appear in eggs until the ovules mature sufficiently to enter the oviduct and become part of an egg. This does not completely preclude involvement of the oviduct in infection as may also occur with S. Enteritidis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the uptake of Salmonella by hen macrophages following bacterial invasion of intestinal cells aids in its dissemination within the host, including in the reproductive organs (11)(12)(13)(14). Contamination of egg contents (yolk, albumen, and eggshell membranes) by S. Enteritidis can occur before oviposition (11,12), where Salmonella colonizing reproductive organs invades and multiplies in the granulosa cells of the preovulatory follicles in the reproductive tract (15,16). Since S. Enteritidis colonization in the ceca of layers results in the transovarian spread of the pathogen to reproductive organs, a decreasing pathogen prevalence in flocks has been reported to result in a direct reduction in human health risk (17).…”
mentioning
confidence: 99%
“…Thorns (34) reported that both a wild-type S. Enteritidis strain and a sefA mutant were able to attach to HEp-2 cells, indicating that multiple determinants may mediate attachment. This is also indicated by differences in mannose sensitivities of various S. Enteritidis strains (30). The results of the Western blot and cell culture attachment assays suggest that the mannose-sensitive binding of JM109(pDUG3A) is due to the presence of SefA in the outer membrane, since JM109 (pTX101) did not possess SefA or show attachment.…”
mentioning
confidence: 81%
“…Attachment assays on avian ovary granulosa and HEp-2 cells were done according to the method of Thiagarajan et al (30), with some modifications. Briefly, granulosa cells were seeded and grown as a monolayer on sterile coverslips and then washed three times with M199 medium (Gibco), and 1 ϫ 10 7 CFU of bacterial cells (grown with and without 1% D-mannose) was added to the coverslips.…”
mentioning
confidence: 99%